Clinical Application of Thromboelastography/Thromboelastometry (TEG/TEM) in the Neonatal Population: A Narrative Review - Konstantinidi, Aikaterini; Sokou, Rozeta; Parastatidou, Stavroula; Lampropoulou, Katerina; Katsaras, George; Boutsikou, Theodora; Gounaris, Antonios K.; Tsantes, Argyrios E.; Iacovidou, Nicoletta (Seminars in Thrombosis and Hemostasis, 2019)
Hemostasis is a dynamic age-related process, which gradually evolves from fetal life throughout childhood until adulthood. Although at birth there is a hemostatic deficit of most coagulation factors, studies have shown that this “hemostatic immaturity” is functionally counterbalanced in healthy term or preterm newborns. This delicate hemostatic balance is, however, deranged in sick neonates, resulting in an enhanced risk of hemorrhage and/or thrombosis. In critically ill neonates, conventional coagulation tests do not seem to provide reliable information or indications regarding the functional status of platelets or fibrinolysis. In contrast, viscoelastic tests, namely thromboelastography/thromboelastometry (TEG/TEM) hold promise for rapid assessment of the whole hemostatic potential, allowing immediate intervention should this be required. However, neonatal data are limited due to lack of reference values, especially in premature neonates. In this narrative review, we provide some insights around current knowledge regarding TEG/TEM applications in healthy and sick newborns. Overall, the use of viscoelastic tests in diagnosis and management of coagulation disorders in neonates is definitely worth further exploration. Consideration should be made to include these tests in the routine laboratory investigation of neonates and specific transfusion algorithms should also be developed in order to avoid treatment pitfalls.
Keywords: hemostasis; thromboelastography/thromboelastometry; conventional coagulation tests; neonates